The relationship between violence, level of functioning, and treatment outcome in psychiatric inpatients. Issue 4 (4th November 2014) - Walji, Irram; Egan, Vincent; Fonseca, Andres; Huxley, Adam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – There is an association between the diagnosis of a mental illness and violent behaviour. Individuals diagnosed with severe and enduring mental health difficulties who display violent behaviour have inferior treatment outcomes when compared with those who do not engage in violent behaviour. Violent behaviour within care settings impacts on general functioning, adherence to treatment plans, and inhibits wider recovery goals. The paper aims to discuss these issues. Design/methodology/approach – This research studied 95 inpatients with a primary diagnosis of severe mental illness, with and without a history of violence, and compared how levels of global functioning and risk impacted on recovery. Patients were divided into two groups: those with and without a previous or current history of violence. The two groups were compared on measures of global functioning, symptomatology, and risk at baseline and 12-month follow up. Findings – Both violent and non-violent groups showed increased global functioning over time, with no significant difference between the groups. Neither group showed significant reductions in risk over time. Patients in the violent group had significantly fewer prior and current symptoms of mental ill-health than non-violent individuals. Research limitations/implications – Despite evidence suggesting that historical or current violence leads to impaired outcomes amongst people with diagnoses of mental illness, the findings of this study suggest a history of violent behaviour was not a predictor of poor progress within inpatient settings. Practical implications – Disconfirming previous hypotheses, the paper suggests that in itself, violent behaviour does not always significantly impair outcomes for individuals diagnosed with mental illnesses, and that many other variables contribute to meaningful recovery. Originality/value – Whilst there are previous studies investigating outcomes for inpatients diagnosed with mental illness who have violent histories, there is a dearth of research comparing equivalent groups in the same facility over the same time period. This study directly compared inpatients with or without a history of violence in the same psychiatric rehabilitation settings.